Superlubricity achieved by polyvinylpyrrolidone at Si3N4/sapphire interfaces - Hongdong Wang; Zhen Luo; Kunpeng Wang; Yuhong Liu; Jianhua Zhang (Friction)
Polymers have complex molecular structures that often lead to interchain friction and hinder movement, making it difficult to achieve superlubricity. However, in the field of hydration lubrication, the electronegative interface of ceramics readily adsorbs water molecules, creating a protective water film that covers the frictional interface and effectively reduces friction. To achieve hydration lubrication, it is essential to create a continuous lubricating film by selectively enriching specific functional groups of adsorbed water molecules from the polymer solution onto the ceramic surface. By adsorbing a hydrophilic layer composed of polyvinylpyrrolidone with pyrrolidone groups onto a negatively charged Si3N4/sapphire interface, we formed a continuous lubricating film. Research has shown that the interaction between the polymer chain structure of polyvinylpyrrolidone molecules (such as PVP10000) in solution and water molecules could result in excellent superlubricity. When the contact pressure exceeds 198 MPa, the coefficients of friction (COF) can be reduced to 0.004–0.007. Through detailed surface analyses and sophisticated simulations, we uncovered the underlying mechanism involved. The pyrrolidone moieties of polyvinyl pyrrolidone (PVP) formed hydrogen bonds with the Si3N4 surface, transforming the initially difficult frictional interface into a PVP/sapphire interface with significantly reduced sliding energy barriers. These findings highlight the vital role of PVP in superlubricity and hydration lubrication and provide a theoretical and experimental basis for the design of materials and lubricants with exceptional lubricating properties.